The 3-3-1 Model with Arbitrarily Charged Leptons - Long, Hoang Ngoc; Loi, Duong Van; Thao, Nguyen Chi; Giang, Thanh Huu Hong (Communications in Physics, 2017)
The gauge model based on \(SU(3)_C\otimes SU(3)_L\otimes U(1)_X\) group with arbitrarily electric charged exotic leptons is presented. The mass eigenvalues and eigenstates for neutral gauge bosons are presented in the general form. We show that in the 3-3-1 models, there always exists triple Higgs self-coupling. The lepton number operator is also presented